Vagueness and law : philosophical and legal perspectives - Keil, Geert; Poscher, Ralf (Oxford : Oxford University Press, 2017)
Bringing together leading scholars working on the topic of vagueness in philosophy and in law, this book fosters a dialogue between philosophers and legal scholars by examining how philosophers conceive vagueness in law from their theoretical perspective and how legal theorists make use of philosophical theories of vagueness.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 9, 2016).
Keywords: Law -- Interpretation and construction; Vagueness (Philosophy); Law; Jurisprudence & general issues